THERAPY OF TYPE 2 DIABETES MELLITUS IN ELDERLY PATIENTS: RISKS AND PROSPECTS - L. Yu. Morgunov (Исследования и практика в медицине)
Diabetes therapy in elderly patients is a complex task due to their heterogeneous population, high risk of hypoglycemic conditions, the development of life-threatening arrhythmias and cardiovascular diseases, dementia, and the presence of a large number of comorbid diseases. The number of elderly patients in the world is growing rapidly, however, the algorithm for the treatment of elderly patients has not yet been developed and preference is given to an individual approach to the therapy of violations of carbohydrate metabolism. There are no therapeutic goals in elderly patients depending on their clinical and functional characteristics, the recommended level of glycated hemoglobin varies in a wide range from 7 to 9%. Priority is the problem of preventing hypoglycemia, which can lead to fatal consequences. The requirements for the use of oral hypoglycemic drugs in elderly patients with diabetes mellitus are also reduced to the absence of nephro-, hepatoand cardiotoxicity, as well as their lack of interaction with other drugs and ease of use. Such conditions are answered by incretin therapy represented by agonists of glucagon-like peptide-1 and inhibitors of dipeptidyl peptidase-4. It is also possible to use ultra-long-acting insulin. It is undesirable to use sulfonylureas and intensive insulin therapy in elderly patients. In the absence of contraindications, the use of metformin and pioglitazone is permissible, with the caution the use of SGLT-2 inhibitors is recommended. Treatment with any medicinal hypoglycemic drugs is possible in elderly patients who lead an active lifestyle and are capable of self-monitoring of carbohydrate metabolism, but in patients with low social adaptation it is desirable to limit the incretin therapy.